Skull vibration induced nystagmus, velocity storage and self-stability - Ian S. Curthoys; David S. Zee; Georges Dumas; Georges Dumas; Christopher J. Pastras; Julia Dlugaiczyk (Frontiers in Neurology, 2025)
In this paper we give an introduction to the area, followed by brief reviews of the neural response to sound and vibration, and then the velocity storage integrator, before putting forward our hypothesis about the neural input to the velocity storage integrator. Finally we discuss some of the implications of our hypothesis. There are two pathways conveying neural information from the vestibular periphery (the semicircular canals and the otoliths) to central neural mechanisms—a direct and an indirect pathway. Within the indirect pathway there is a unique neural mechanism called the velocity storage integrator (VSI) which is part of a neural network generating prolonged nystagmus, afternystagmus and the sensation of self-motion and its converse self-stability. It is our hypothesis that only neural input from primary afferent neurons with irregular resting discharge projects in the direct pathway, whereas the primary afferent input in the indirect pathway consists of neurons with regular resting discharge. The basis for this hypothesis is that vibration is a selective stimulus for vestibular neurons with irregular resting discharge. 100 Hz mastoid vibration, while capable of generating nystagmus (skull vibration induced nystagmus SVIN), is ineffective in generating afternystagmus (in the condition of an encased labyrinth) which is a marker of the action of the VSI, leading to the conclusion that irregular afferents bypass the indirect pathway and the VSI. In order to present this hypothesis we review the evidence that irregular neurons are selectively activated by sound and vibration, whereas regular neurons are not so activated. There are close similarities between the temporal characteristics of the irregular afferent neural response to vibration and the temporal characteristics of SVIN. SVIN is a simple clinical indicator of whether a patient has an imbalance between the two vestibular labyrinths and our hypothesis ties SVIN to irregular primary vestibular neurons.